Chemical and mechanical defenses vary among maternal lines and leaf ages in Verbascum thapsus L. (Scrophulariaceae) and reduce palatability to a generalist insect - Alba, Christina, author; Bowers, M. Deane, author; Blumenthal, Dana, author; Hufbauer, Ruth A., author; Public Library of Science, publisher (Colorado State University. Libraries, 2014)
Intra-specific variation in host-plant quality affects herbivore foraging decisions and, in turn, herbivore foraging decisions mediate plant fitness. In particular, variation in defenses against herbivores, both among and within plants, shapes herbivore behavior. If variation in defenses is genetically based, it can respond to natural selection by herbivores. We quantified intra-specific variation in iridoid glycosides, trichome length, and leaf strength in common mullein (Verbascum thapsus L, Scrophulariaceae) among maternal lines within a population and among leaves within plants, and related this variation to feeding preferences of a generalist herbivore, Trichopulsia ni Hübner. We found significant variation in all three defenses among maternal lines, with T. ni preferring plants with lower investment in chemical, but not mechanical, defense. Within plants, old leaves had lower levels of all defenses than young leaves, and were strongly preferred by T. ni. Caterpillars also preferred leaves with trichomes removed to leaves with trichomes intact. Differences among maternal lines indicate that phenotypic variation in defenses likely has a genetic basis. Furthermore, these results reveal that the feeding behaviors of T. ni map onto variation in plant defense in a predictable way. This work highlights the importance of variation in host-plant quality in driving interactions between plants and their herbivores.
Keywords: seeds; plant-herbivore interactions; plant defenses; caterpillars; glycosides; leaves; herbivory; trichomes